Implementation of Enterprise Risk Management (ERM) Framework in Enhancing Business Performances in Oil and Gas Sector - Sanmugam Annamalah; Murali Raman; Govindan Marthandan; Aravindan Kalisri Logeswaran (Economies, 2018)
This study empirically investigated the ERM Implementation model and proposed framework to identify and manage risks in Oil and Gas Sector in Malaysia. The study examined the role of ERM framework implementation in improving business performance by utilizing Economic Value Added as a measurement tool. The study also provides insights to the Oil and Gas Sector to gain higher profit returns, reduce cost of capital, and improve shareholders value. Moreover, it contributes significantly in the field of Enterprise risk management in Malaysia. The identification and management of risk is significant to organizations in managing risks efficiently. Expectations of stakeholders of the organization are high from executives and board of directors in managing the risk effectively. Linear regression analysis is utilized in analyzing the data obtained from the data collection performed for this paper. Purposive sampling has been employed in order to select the firms that are operating in Malaysian oil and gas sector. Primary data has been utilized to collect data with the help of structured questions and interview techniques that involve semi structured questions. The results of the regression analysis conducted for in this study suggested that a significant and positive relationship between Enterprise Risk Management with operational risk; market risk; political risk; health, safety and environmental risk; and, also business performance.